Iliopsoas the Hidden Muscle: Anatomy, Diagnosis, and Treatment. Issue 6 (June 2020) - Lifshitz, Liran; Bar Sela, Shlomo; Gal, Noga; Martin, RobRoy; Fleitman Klar, Michal
Abstract : Abstract: The iliopsoas is a deep muscle group which anatomically connects the spine to the lower limbs. It is composed of the iliacus, psoas major, and psoas minor muscles. The iliopsoas functions as the primary hip flexor. Because the iliopsoas is important for daily activities, including sports, impairments and pathology associated with this muscle group can cause significant limitations. Evaluating pathology associated with the iliopsoas muscle group can be challenging because the patient's complaints are often vague and difficult to discern from other hip problems. This article will review relevant anatomy, discuss common pathologies, present clinical based examination methods, and outline conservative treatment interventions focusing on manual therapy and active exercises.